Environmental information disclosure and stock price crash risk: Evidence from China - Ge, Yongbo; Chen, Qi; Qiu, Shiwen; Kong, Xiaoran (Frontiers in Environmental Science, 2023)
Environmental performances have gained great prominence for firms in recent years. This paper empirically tests the relationship between environmental information disclosure and the risk of stock price crashes based on a sample of Chinese A-share listed firms from 2013–2018. The results show that environmental information disclosure has a significant negative correlation with stock price crash risk, with mechanism analysis showing that media coverage plays an intermediary role between them. Further analysis finds that: first, the inhibitory effect of environmental information disclosure on stock price crashes is more significant in companies with a lower proportion of independent directors, which reflects the supervision effect of environmental information disclosure. Second, the role of environmental information disclosure has a greater negative impact on the risk of stock price crashes in industries with low competition, indicating that environmental information disclosure is not a tool for enterprises to compete for resources. Third, the profit motivation of institutional investors restrains the negative impact of environmental information disclosure on price collapse risk. Forth, the level of government environmental governance is an important support for enterprise environmental information disclosure.